2001
DOI: 10.1088/0022-3727/34/11/308
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear susceptibilities, absorption coefficients and refractive indices of colloidal metals

Abstract: The investigations of the nonlinear optical parameters of Au, Ag, Pt and Cu colloidal solutions using the Z-scan method and third-harmonic generation (THG) are presented. The nonlinear refractive indices, nonlinear absorption coefficients and Kerr-induced nonlinear susceptibilities (χ(3)(-ω;ω,-ω,ω)) of these solutions on the wavelengths of picosecond and nanosecond Nd:YAG laser radiation (λ = 1064 nm) and its second harmonic (λ = 532 nm) have been measured. A tenfold increase of nonlinear susceptibilities on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(85 citation statements)
references
References 29 publications
3
81
0
1
Order By: Relevance
“…Exact values for the nonlinear refractive indices or the nonlinear susceptibilities of gold and other materials are already obtainable experimentally. The investigation methods usually rely on z-scan absorption measurements or the evaluation of low-order harmonic light generation [109,110,111,112,113]. The utilization of the fifth-order harmonic generation in nanostructures, as it is demonstrated here, will offer a new means of investigating nonlinear optical properties of metals and other materials in terms of higher nonlinear orders and shorter wavelengths in the ultraviolet spectral range.…”
Section: Surface-enhanced Low-order Harmonic Generationmentioning
confidence: 99%
“…Exact values for the nonlinear refractive indices or the nonlinear susceptibilities of gold and other materials are already obtainable experimentally. The investigation methods usually rely on z-scan absorption measurements or the evaluation of low-order harmonic light generation [109,110,111,112,113]. The utilization of the fifth-order harmonic generation in nanostructures, as it is demonstrated here, will offer a new means of investigating nonlinear optical properties of metals and other materials in terms of higher nonlinear orders and shorter wavelengths in the ultraviolet spectral range.…”
Section: Surface-enhanced Low-order Harmonic Generationmentioning
confidence: 99%
“…2, 3, 4, and 5) include the parameters in Eqs. (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). In contrast to the previous works, changes in the characteristics of domains are studied under the action of pulsed laser radiation with the duration 1000 times longer (τ=20 ns) than in [6,7] at the wavelength corresponding to the maximum of the extinction (plasmonic) spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that these experimental results were very different. In particular, the nonlinear refractive index in picosecond pulses was much lower than in nanosecond pulses despite high radiation intensity [10].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This has already been highlighted in various experimental works. By applying the z-scan technique in the time-resolved off-axis scheme Ganeev et al have demonstrated the presence of a thermal lens effect in the third-order nonlinear response of metal nanoparticles in the nanosecond pulse regime and its absence in the picosecond regime [102]. Liao et al have also invoked thermal effects to explain the discrepancies observed between different pulse temporal regimes [103].…”
Section: Application To the Nonlinear Response: Thermal Lens Contribumentioning
confidence: 99%